STRUKTUR ATOM BERDASARKAN ILMU KIMIA DAN PERSPEKTIF AL-QURAN - Sabarni Sabarni (UIN AR-RANIRY, 2019)
The atomic structure is one of the chemical metrics studied in high schools and universities. The concept of atomic structure in learning chemistry in schools and universities is usually not associated with religion, especially the Qur'an, so as if learning atomic structure is a separate science and has no connection with the Qur'an. To show that the Qur'an is a guideline for humanity, including examining the natural sciences including chemistry, the authors want to examine the concept of atomic structure based on chemistry and the perspective of the Qur'an which aims to determine the concept of the development of atomic models, particles basic and electron configurations based on chemistry and the Qur'anic perspective. The data collection technique used in this study is literature (Library Research), namely studying the Qur’an and studying reading books, journals, dictates, dictionaries, and scientific works. From this study shows that the Qur'an has been proven to explain the concept of atomic structure first and in the Qur'an there is the concept of atomic structure which is in line with the chemical concept proposed by chemists.